P. 1
solutions to homework 5, jackson e&m, for graduate e&m physics class

# solutions to homework 5, jackson e&m, for graduate e&m physics class

4.0

|Views: 2,040|Likes:
solutions to some jackson e&m homework problems
solutions to some jackson e&m homework problems

See more
See less

11/08/2015

pdf

text

original

# Assignment 5 — Solutions 2/13/04 (revised 2/23/04

)
Problem 3.10
(a) We get to integrate our relations from last time. J oy.
VHf, zL = :
V , -pê 2< f < pê 2
-V , pê 2< f < 3pê 2
A
0n
=
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
p L I
m
Hn p bê LL

-pê2
3pê2
f

0
L
z VHf, zL sinJ
n p z
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
L
N
:
A
mn
B
mn
> =
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
p L I
m
Hn p b ê LL

-pê2
3pê2
f

0
L
z VHf, zL :
cosmf
sinmf
> sinJ
n p z
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
L
N , m ∫ 0
The range of f integration has been shifted to be convenient for V (can be done since it's periodic). For m, n ∫ 0:
:
A
mn
B
mn
> =
2V
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
p L I
m
Hn p bê LL

0
L
z sinJ
n p z
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
L
N
i
k
j
j
j

-pê2
pê2
f-

pê2
3pê2
f
y
{
z
z
z :
cosmf
sinmf
>
=
2V
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
p L I
m
Hn p bê LL
B-
L
ÅÅÅÅÅÅÅÅÅÅÅ
n p
cosJ
n p z
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
L
NF
0
L

1
ÅÅÅÅÅÅÅ
m
Ä
Ç
Å
Å
Å
Å
Å
Å
Å
ÅÅ
:
sinmf
-cosmf
>
-pê2
pê2
- :
sinmf
-cosmf
>
pê2
3pê2
É
Ö
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
ÑÑ
=
-2V
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
n mp
2
I
m
Hn p bê LL
@H-1L
n
-1D :
2sinHmpê 2L - sinH3mpê 2L + sinHmpê 2L
0+ cosH3mpê 2L - cosHmpê 2L
>
=
2V @1-H-1L
n
D
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
n mp
2
I
m
Hn p bê LL
:
4sinHmpê 2L
0
>
A useful table from the CRC handbook of Standard Mathematical Tables and Formulae (30th edition):
n œ  n even n odd n ê 2odd nê 2even
sinn p 0 0 0 0 0
cosn p H-1L
n
+1 -1 +1 +1
sinn pê 2 0 H-1L
Hn-1Lê2
0 0
cosn pê 2 H-1L
nê2
0 -1 +1
from which we deduce that A
mn
= 0 for even m and A
mn
∂ H-1L
Hm-1Lê2
for odd m. A
m0
= 0= B
m0
from
sinHn p z ê LL§
n=0
= 0 and B
0n
= 0 since sinmf§
m=0
= 0. Also A
0n
= 0 because the f integral is over VHf, zL only
which is odd in the given range. Since A
mn
∂ 1- H-1L
n
it vanishes for even n, and the factor is 2 for odd n.
Finally:
A
mn
=
16V H-1L
Hm-1Lê2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅ
n m p
2
I
m
Hn p bê LL
, n, modd ; all other coefficients vanish
1
FHv, f, zL =
16V
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
p
2

n,modd
H-1L
Hm-1Lê2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
n mp
2
I
m
Hn p bê LL
cosHmfL sinJ
n p z
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
L
N IJ
n p v
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
L
N
(b) For b ê L `1, which means vê L `1 since v§ b, we have from the asymptotic expansion 3.102:
I
m
Hn p vê LL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
I
m
Hn p b ê LL
º
Hn p vê 2LL
m
ê H2m+ 2L!
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅ
Hn p b ê 2LL
m
ê H2m+ 2L!
º J
v
ÅÅÅÅÅÅÅÅ
b
N
m
One might worry that the arguments to I
m
are not strictly always small since n ranges to infinity, but in a com-
pletely handwaving manner one may hope that the effects of increasing n in numerator and denominator magi-
cally cancel out. For those of you who are rightly dubious you can probably go to the series expansion (Gradsh-
teyn and Ryzhik 8.445):
I
n
HzL = ‚
k=0

1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅ
k ! GHn + k + 1L
J
z
ÅÅÅÅÅ
2
N
n+2k
(exact)
and use the binomial theorem etc. to figure out the specifics. If you manage do please tell. Anyway at z = Lê 2
and seeing from our table that sinHn pê 2L§
n odd
= H-1L
Hn-1Lê2
:
FHv, f, zL º
16V
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
p
2

n,modd
H-1L
Hm-1Lê2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅ
n mp
2
H-1L
Hn-1Lê2
cosHmfL J
v
ÅÅÅÅÅÅÅÅ
b
N
m
=
16V
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
p
2

n=0

H-1L
n
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ
2n + 1

m=0

H-1L
m
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
2m+ 1
cos@H2m+ 1L fD J
v
ÅÅÅÅÅÅÅÅ
b
N
2m+1
=
16V
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
p
2

p
ÅÅÅÅÅÅ
4

m=0

H-1L
m
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
2m+ 1

1
ÅÅÅÅÅ
2
I‰
Â H2m+1L f
+ ‰
-Â H2m+1L f
M J
v
ÅÅÅÅÅÅÅÅ
b
N
2m+1
=
2V
ÅÅÅÅÅÅÅÅ ÅÅÅÅ
p

m=0

H-1L
m
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
2m+ 1
BJ‰
Â f

v
ÅÅÅÅÅÅÅÅ
b
N
2m+1
+ J‰
-Â f

v
ÅÅÅÅÅÅÅÅ
b
N
2m+1
F
=
2V
ÅÅÅÅÅÅÅÅ ÅÅÅÅ
p
Btan
-1
J‰
Â f

v
ÅÅÅÅÅÅÅÅ
b
N + tan
-1
J‰
-Â f

v
ÅÅÅÅÅÅÅÅ
b
NF
Looking up the math handbook (do the trig if you like) gives tan
-1
z
1
≤ tan
-1
z
2
= tan
-1
@Hz
1
≤ z
2
L ê H1¡ z
1
z
2
LD:
FHv, f, zL º
2V
ÅÅÅÅÅÅÅÅ ÅÅÅÅ
p
tan
-1
i
k
j
j
j
j

Â f
vê b + ‰
-Â f
vê b
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
1- H‰
Â f
vê bL H‰
-Â f
vê bL
y
{
z
z
z
z
=
2V
ÅÅÅÅÅÅÅÅ ÅÅÅÅ
p
tan
-1
i
k
j
jj
2Hvê bL cosf
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
1- v
2
ê b
2
y
{
z
zz
Exactly as you should have found in 2.13. Note the shorter route to summing the series, those of you who're
interested.
2
Problem 3.11
(a) The standard way to show orthogonality is to integrate the differential equation, in this case 3.77:
0 =

2
J
n
HxL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
x
2
+
1
ÅÅÅÅÅ
x

J
n
HxL
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅ
x
+
i
k
j
j
j
j
1-
n
2
ÅÅÅÅÅÅÅÅÅ
x
2
y
{
z
z
z
z
J
n
HxL =
1
ÅÅÅÅÅ
x

ÅÅÅÅÅÅÅÅÅ
x

i
k
j
jx

ÅÅÅÅÅÅÅÅÅ
x
J
n
HxL
y
{
z
z +
i
k
j
j
j
j
1-
n
2
ÅÅÅÅÅÅÅÅÅ
x
2
y
{
z
z
z
z
J
n
HxL
(1) 0 =
1
ÅÅÅÅÅÅ
r

ÅÅÅÅÅÅÅÅÅÅ
r

i
k
j
j
jr

ÅÅÅÅÅÅÅÅÅÅ
r
J
n
Hk rL
y
{
z
z
z +
i
k
j
j
j
j
k
2
-
n
2
ÅÅÅÅÅÅÅÅÅ
r
2
y
{
z
z
z
z
J
n
Hk rL
Act on both sides with the integral operator
Ÿ
0
a
r r J
n
H rL and integrate stuff by parts:
0 =

0
a
r

ÅÅÅÅÅÅÅÅÅÅ
r

i
k
j
j
jr

ÅÅÅÅÅÅÅÅÅÅ
r
J
n
Hk rL
y
{
z
z
z J
n
H rL +

0
a
r
i
k
j
j
j
j
r k
2
-
n
2
ÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
z
J
n
Hk rL J
n
H rL
y
{
z
z
z
z
=
Ä
Ç
Å
Å
Å
Å
Å
Å
Å
Å
r J
n
H rL

ÅÅÅÅÅÅÅÅÅÅ
r
J
n
Hk rL
É
Ö
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
0
a
-

0
a
r r
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r

J
n
H rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
r
+

0
a
r
i
k
j
j
j
j
r k
2
-
n
2
ÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
z
J
n
Hk rL J
n
H rL
y
{
z
z
z
z
We're given that the first term vanishes at the lower limit r = 0 (is it just me or is this trivial, because r = 0 at
r = 0??). The other condition says
(2)

ÅÅÅÅÅÅÅÅÅÅ
r
ln@J
n
Hk rLD
ƒ
ƒ
ƒ
§
ƒ
ƒ
ƒ
r=a
=
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ
J
n
Hk rL

J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
ƒ
ƒ
ƒ
§
ƒ
ƒ
ƒ
r=a
= -
l
ÅÅÅÅÅÅ
a
ï r
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
ƒ
ƒ
ƒ
§
ƒ
ƒ
ƒ
r=a
= -l J
n
Hk aL
Incidentally we see from this that k is restricted to values such that (2) is satisfied, i.e. k a ª y
nn
such that
a J
n
£
Hy
nn
L + l J
n
Hy
nn
L = 0. We can arbitrarily start numbering eigenvalues n = 1, 2, ….
0 = -l J
n
H aL J
n
Hk rL -

0
a
r r
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r

J
n
H rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
r
+

0
a
r
i
k
j
j
j
j
r k
2
-
n
2
ÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
z
J
n
Hk rL J
n
H rL
y
{
z
z
z
z
0 = -l J
n
Hk aL J
n
H rL -

0
a
r r
J
n
H rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
r

J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
+

0
a
r
i
k
j
j
j
j
r 
2
-
n
2
ÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
z
J
n
H rL J
n
Hk rL
y
{
z
z
z
z
In the last step I've just renamed k ¨. Subtracting the second line from the first gives what we want:
0 =

0
a
r r Ik
2
-
2
M J
n
Hk rL J
n
H rL = Ik
2
-
2
M

0
a
r r J
n
Hk rL J
n
H rL
since it means that unless k
2
= 
2
(in which case the right-hand-side is trivially 0) the integral must vanish.
(b) Now normalization. This time act on (1) with
Ÿ
0
a
r r
2
J
n
Hk rL ê r and use f
f
ÅÅÅÅÅÅÅÅÅ
r
=
1
ÅÅÅÅÅ
2

H f
2
L
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
r
:
3
(3)
0 =

0
a
r
i
k
j
j
jr
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r

ÅÅÅÅÅÅÅÅÅÅ
r

i
k
j
j
jr
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z + Ik
2
r
2
- n
2
M J
n
Hk rL
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
=
1
ÅÅÅÅÅ
2

0
a
r

ÅÅÅÅÅÅÅÅÅÅ
r

i
k
j
j
jr
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
2
+ k
2

0
a
r r
2
J
n
Hk rL
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
-
n
2
ÅÅÅÅÅÅÅÅÅ
2

0
a
r

ÅÅÅÅÅÅÅÅÅÅ
r
@J
n
Hk rLD
2
Integrate the second term by parts:
k
2

0
a
r r
2
J
n
Hk rL
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
= k
2
Ar
2
J
n
2
Hk rLE
0
a
- k
2

0
a
r J
n
Hk rL

ÅÅÅÅÅÅÅÅÅÅ
r
Ar
2
J
n
Hk rLE
= k
2
a
2
J
n
2
Hk aL -2k
2

0
a
r r J
n
Hk rL J
n
Hk rL
-k
2

0
a
r J
n
Hk rL r
2

J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
Move the last term to the left, divide everything by 2, and we get
k
2

0
a
r r
2
J
n
Hk rL
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
=
1
ÅÅÅÅÅ
2
k
2
a
2
J
n
2
Hk aL - k
2

0
a
r r J
n
Hk rL J
n
Hk rL
Getting back to (3), and using (2) to get rid of the derivative in the evaluation of the first term at r = a:
0 =
1
ÅÅÅÅÅ
2
Ä
Ç
Å
Å
Å
Å
Å
Å
Å
Å
Å
i
k
j
j
jr
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
2
É
Ö
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
0
a
+
1
ÅÅÅÅÅ
2
k
2
a
2
J
n
2
Hk rL - k
2

0
a
r r J
n
Hk rL J
n
Hk rL -
n
2
ÅÅÅÅÅÅÅÅÅ
2
AJ
n
2
Hk rLE
0
a
=
l
2
ÅÅÅÅÅÅÅÅÅ
2
J
n
2
Hk aL +
1
ÅÅÅÅÅ
2
k
2
a
2
J
n
2
Hk aL - k
2

0
a
r r J
n
Hk rL J
n
Hk rL -
n
2
ÅÅÅÅÅÅÅÅÅ
2
J
n
2
Hk aL +
n
2
ÅÅÅÅÅÅÅÅÅ
2
J
n
2
H0L
Note that J
n
H0L is not generally 0! For instance J
0
H0L = 1 which we can see from the series expansion 3.82.

0
a
r r J
n
2
Hk rL =
a
2
ÅÅÅÅÅÅÅÅÅ
2

i
k
j
j
j
j
1+
l
2
- n
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
k
2
a
2
y
{
z
z
z
z
J
n
2
Hk aL +
n
2
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ
2k
2
J
n
2
H0L
Actually it is more useful for later comparison to leave the derivative as is:

0
a
r r J
n
2
Hk rL =
a
2
ÅÅÅÅÅÅÅÅÅ
2

i
k
j
j
j
j
1-
n
2
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
k
2
a
2
y
{
z
z
z
z
J
n
2
Hk aL +
a
2
ÅÅÅÅÅÅÅÅÅ
2

i
k
j
j
j
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
2
+
n
2
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ
2k
2
J
n
2
H0L
In general proving completeness of a set of functions is a lengthy process which I will forego here. Consult a
math handbook if you're interested, for instance chapter 9 of Arfken which deals with Sturm-Liouville theory. In
our case the differential operator in (1) can be put into self-adjoint form by multiplying it by x:
x

2
J
n
HxL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ
x
2
+
J
n
HxL
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅ
x
+
i
k
j
j
j
j
x -
n
2
ÅÅÅÅÅÅÅÅÅ
x
y
{
z
z
z
z
J
n
HxL = 0
4
Now the necessary and sufficient condition for self-adjointness is that p
£
HxL = qHxL where pHxL = x is the coeffi-
cient of the second-order term and qHxL = 1 the coefficient of the first-order term, which is obviously satisfied. In
Quantum Mechanics terminology a self-adjoint operator is Hermetian, and just as in there their eigenfunctions
form a complete set. With this in mind we can write
f HrL = ‚
n=1

A
n
J
n
J
y
nn
r
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
a
N where a J
n
£
Hy
nn
L -l J
n
Hy
nn
L = 0
To extract A
n
we do the usual acting on both side with
Ÿ
0
a
r r J
n
Hy
nn
rê aL:

0
a
r f HrL r J
n
J
y
nn
r
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
a
N = ‚
m=1

A
m

0
a
r r J
n
J
y
nn
r
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
a
N J
n
J
y
nm
r
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅ
a
N
= „
m=1

A
m
d
mn
Ä
Ç
Å
Å
Å
Å
Å
Å
Å
Å
ÅÅ
a
2
ÅÅÅÅÅÅÅÅÅ
2

i
k
j
j
j
j
1-
n
2
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
k
2
a
2
y
{
z
z
z
z
J
n
2
Hk aL +
a
2
ÅÅÅÅÅÅÅÅÅ
2

i
k
j
j
j
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
2
+
n
2
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ
2k
2
J
n
2
H0L
É
Ö
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
ÑÑ
A
n
=
2
ÅÅÅÅÅÅÅÅÅ
a
2
Ä
Ç
Å
Å
Å
Å
Å
Å
Å
Å
ÅÅ
i
k
j
j
j
j
1-
n
2
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
k
2
a
2
y
{
z
z
z
z
J
n
2
Hk aL +
i
k
j
j
j
J
n
Hk rL
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
r
y
{
z
z
z
2
+
n
2
a
2
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
4k
2
J
n
2
H0L
É
Ö
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
Ñ
ÑÑ
-1

0
a
r f HrL r J
n
J
y
nn
r
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
a
N
If you find out what J ackson did with the J
n
2
H0L term please let me know.
Problem 3.12
(a) In cylindrical coordinates we can expand F as in 3.106 (remember that we want finiteness for all of
z ¥ 0). Since we have azimuthal symmetry it must be that there is no f dependence, i.e. all the A
m
's and B
m
's
vanish except for B
0
ª AHkL:
FHv, f, zL =

0

k AHkL ‰
-k z
J
0
Hk vL
Using the orthogonality condition 3.108 and the z = 0 boundary condition F§
z=0
= V QHv- aL, act on both sides
with
Ÿ
0

v vJ
0
H vL at z = 0:

0

v FHv, f, zL vJ
0
H vL =

0

k AHkL

0

v vJ
0
Hk vL J
0
H vL
V

0
a
v vJ
0
H vL =

0

k AHkL
1
ÅÅÅÅÅ
k
dH - kL =
1
ÅÅÅÅÅ

AHL
AHkL = k V

0
a
v vJ
0
Hk vL
From Gradshteyn and Ryzhik 5.52 (W is any of N, H
H1L
or H
H2L
):
5

x x
n+1
W
n
HxL = x
n+1
W
n+1
HxL
Changing integration variables for AHkL to x ª k v, so x ª k v:
AHkL =
V
ÅÅÅÅÅÅÅ
k

0
k a
x x J
0
HxL =
V
ÅÅÅÅÅÅÅ
k
x J
1
HxL
0
k a
= a V J
1
Hk aL
FHv, f, zL = a V

0

k J
1
Hk aL ‰
-k z
J
0
Hk vL
(b) Perpendicular above the center of the disk means v= 0. Using J
0
H0L = 1and Gradshteyn and Ryzhik
6.611:

0

x ‰
-a x
J
n
Hb xL =
b
-n
I
è!!!!!!!!!!!!!!!!
a
2
+ b
2
- aM
n
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
è!!!!!!!!!!!!!!!!
a
2
+ b
2
, Ren > -1andReHa ≤ Â bL > 0
FH0, f, zL = a V

0

k J
1
Hk aL ‰
-k z
= a V
è!!!!!!!!!!!!!!!
z
2
+ a
2
- z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅ
a
è!!!!!!!!!!!!!!!
z
2
+a
2
= V
i
k
j
j
j
j
1-
z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅ
è!!!!!!!!!!!!!!!
a
2
+ z
2
y
{
z
z
z
z
(c) Above the edge is at v= a. Setting n = 0 in 3.87, we find that W
-1
= W
+1
[as an aside: W
-n
= H-1L
n
W
n
holds for arbitrary n œ ]. Setting n = 0 in 3.88, we find 2W
0
£
= W
-1
- W
+1
= -2W
1
. Thus J
1
HxL = -J
0
HxL ê x:
FHa, f, zL = a V

0

k J
1
Hk aL ‰
-k z
J
0
Hk aL = -a V

0

k J
0
Hk aL ‰
-k z

ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅ
Hk aL
J
0
Hk aL
= -V A‰
-k z
J
0
2
Hk aLE
0

+ a V

0

k J
0
2
Hk aL

ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅ
Hk aL

-k z
+a V

0

k J
0
£
Hk aL ‰
-k z
J
0
Hk aL
From 3.91 we know that J
0
Hk aL remains finite as k Ø¶, so the upper limit of the first term is just 0. Also we
move the last term to the other side and get
-2a V

0

k J
0
£
Hk aL ‰
-k z
J
0
Hk aL = V J
0
2
H0L + a V

0

k J
0
2
Hk aL
z
ÅÅÅÅÅ
a

-k z
Recall that J
0
H0L = 1. From Gradshteyn and Ryzhik 6.612:

0

x ‰
-a x
J
0
2
Hb xL =
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅ
p
è!!!!!!!!!!!!!!!!!!!
a
2
+ 4b
2
K
i
k
j
j
j
jj
2b
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ
è!!!!!!!!!!!!!!!!!!!
a
2
+ 4b
2
y
{
z
z
z
zz
FHa, f, zL =
V
ÅÅÅÅÅÅÅ
2
+
V z
ÅÅÅÅÅÅÅÅ ÅÅÅÅ
2

2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ
p
è!!!!!!!!!!!!!!!!!!
z
2
+ 4a
2
K
i
k
j
j
j
j
2a
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅ
è!!!!!!!!!!!!!!!!!!
z
2
+ 4a
2
y
{
z
z
z
z
FHa, f, zL =
V
ÅÅÅÅÅÅÅ
2

i
k
j
j1+
z k
ÅÅÅÅÅÅÅÅÅÅÅ
p a
KHkL
y
{
z
z , k ª
2a
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅ
è!!!!!!!!!!!!!!!!!!
z
2
+ 4a
2
6

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->